Antiphospholipid syndrome. Issue 1 (February 2020) - Sammaritano, Lisa R.
Abstract: Antiphospholipid syndrome is an autoimmune systemic disorder characterized by arterial, venous, or small vessel thrombosis and/or recurrent early pregnancy loss, fetal loss, or pregnancy morbidity in the setting of documented persistent antiphospholipid antibodies that include the lupus anticoagulant, or moderate-high titer anticardiolipin, or anti -β2Glycoprotein I antibodies. Associated clinical manifestations include livedo reticularis, cutaneous ulcerations, thrombocytopenia, hemolytic anemia, valvular heart disease, and nephropathy. The degree of risk associated with antiphospholipid antibody depends on the characteristics of the antiphospholipid antibody profile and on the presence of additional thrombotic risk factors. Current standard treatment for unprovoked thrombosis is long-term warfarin or other vitamin K antagonist therapy. Treatment to prevent recurrent obstetric complications is low-dose aspirin and prophylactic heparin, usually low-molecular-weight heparin. Optimal treatment for standard therapy failures or for certain nonthrombotic manifestations is uncertain, although nonanticoagulation therapies that address multiple demonstrated mechanisms of disease are being explored.